Assessment of Knowledge, Attitudes and Practices towards Nutrition amongst Adolescents in Karachi - Kashaf Aqeel Zaidi; Wajeeha Mahmood; Farah Ahmad (ziauddin University, 2024)
Background: The association between health and nutrition are eminent. Quality nutrition is acknowledged as one of the most important determinants of optimal development, good health, and wellbeing. Therefore, the study aimed to determine the knowledge, attitudes, and practices amongst adolescents regarding nutrition. Methods: It was a cross-sectional study conducted between 2016 to 2017 in Karachi. The sample size was 384; the purposive sampling technique was applied with a target population of adolescents between 14 and 19 years of age. Informed consent was taken before the questionnaire submission. Data were collected via self-administered questionnaires from students of various schools in Karachi. The Chi square test was applied for associations and a p-value of <0.05 was considered statistically significant. Results: The mean age of 394 adolescents was (mean±SD) 17.08 ± 1.63 years and found female predominance 282(71.6%). The average weight of the participants was 58.60 ± 18.58. Protein 305(77.4%) was the most widely consumed food. Breakfast was seen as the most important meal of the day among 213(54.1%) all participants. There was a significant association between healthy dietary habits and the frequency of exercise per week (p-value=0.001). Only 57(14.5%) followed a specific meal plan and the mostly 151(38.3%) not following a meal plan was due to lack of time. Conclusion: Most of the adolescents 87(22.2%) understand the importance of various food nutrients. However, appropriate nutritional practices were not found in the majority of the adolescents, possibly due to the lack of time and sedentary lifestyle. Keywords: Nutritional Quality; Adolescent Medicine; Non-Communicable Diseases.